2010
DOI: 10.1007/s12291-010-0075-1
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase in Chronic Kidney Disease

Abstract: Numerous lines of evidence implicate a role of myeloperoxidase (MPO) in the pathogenesis of cardiovascular disease (CVD). It is a well accepted fact that patients with chronic kidney disease (CKD) are at an increased risk for CVD. MPO is a pro-oxidant enzyme which could be involved in the increased susceptibility of these patients to CVD. Hence, the levels of plasma MPO was determined in healthy controls as well as in patients with CKD [stratified with the level of their kidney failure as CKD stages II-V (end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 17 publications
(11 reference statements)
1
18
1
Order By: Relevance
“…In an observation of 41 non-dialysis CKD patients, Caimi et al did not see any significant association between myeloperoxidase circulating levels and serum creatinine or GFR [37]. In another observation of 100 patients at different stages of CKD, Madhusudhana et al reported even a graded decrease in plasma myeloperoxidase from stage 1 to stage 5 [36]. This is in contrast with the report of Capeillere-Blandin et al who showed a significantly higher level of myeloperoxidase in ESKD patients on hemodialysis when compared to non-dialysis CKD patients [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an observation of 41 non-dialysis CKD patients, Caimi et al did not see any significant association between myeloperoxidase circulating levels and serum creatinine or GFR [37]. In another observation of 100 patients at different stages of CKD, Madhusudhana et al reported even a graded decrease in plasma myeloperoxidase from stage 1 to stage 5 [36]. This is in contrast with the report of Capeillere-Blandin et al who showed a significantly higher level of myeloperoxidase in ESKD patients on hemodialysis when compared to non-dialysis CKD patients [40].…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear, if myeloperoxidase activity and level could in part explain the added cardiovascular burden in advancing CKD, as the association of myeloperoxidase level with different stages of CKD has not been systematically investigated. Although, studies suggest higher rate of mortality and CV outcomes in association with higher myeloperoxidase levels in dialysis patients [34,35], other studies show normal or even decreasing level of myeloperoxidase at higher stages of CKD [36,37]. Such a discrepancy in myeloperoxidase distribution by CKD stage may be a reflection of dissociation between myeloperoxidase level and its activity in non-dialysis CKD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent study demonstrates that MPO deficiency ameliorates renal injury in the renal ablation model of CKD in mice [ 50 ]. Another study reports a negative correlation between MPO and urea and creatinine levels [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conservatively treated clinically stable CKD patients, serum MPO was reported to be normal [ 42 ] and even decreasing with aggravation of kidney function [ 43 ]. In patients who were already on renal replacement therapy, either HD or continuous ambulatory peritoneal dialysis (CAPD), basal serum MPO activity or concentration was reported to increase, with the highest values found in CAPD [ 28 , 44 , 45 ].…”
Section: Mpo and Renal Replacement Therapy In Ckdmentioning
confidence: 99%